MODEL PEMBINAAN PEDAGANG KAKI LIMA DI KOTA SURAKARTA (Upaya Mendukung Program Aksi Kota Kreatif) - Suwandi, Joko; Sutrisno, Budi (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2017)
The research aimed to describe the model of PKL coaching held by Surakarta City Government in the shape of arranging coaching (empowerment) model with several programmed and sustainable approaches, so that it could assure people economic activity settlement and support city development program, including Creative City Action Program. This study explored and described PKL coaching clinic held by Surakarta City Government, and the result would be a material for appropriate coaching model development. The data collection methods were documentation and in-depth interview with key source person, after that the data to be analyzed with SWOT and critical analysis.Â The results revealed: 1) coaching and counseling in the shape of PKL is currently not effective; 2) the program cannot fully assist to get capital loan. 3) The City Government provides shelter, chart, tent, and umbrella as free facilities; 4) The SIP will be issued soon; 5) administer events that involving PKL such as night selling centre GALABO, Night market in Ngarsopuro, Car Free Day in Slamet Riyadi and Pucangsawit street, Sunday Market in Manahan Stadium.